Social Organization Is Associated With Relaxed Selection on Worker Genes in Highly Polygyne Ants - Kailey Ferger; Neil D. Tsutsui (Ecology and Evolution)
ABSTRACT Ants display a diversity of social structures reflected by differences in caste, nest, and colony organization. Previous research has shown that highly eusocial insects (Hymenoptera) exhibit genome‐wide signatures of relaxed selection due to their smaller effective population sizes. However, it is unknown how the colony structure itself may shape the evolution of eusocial species through its effects on the worker caste. Worker ants are typically sterile or produce only male offspring, so traits affecting their behavior evolve mainly through kin selection. Kin selection is predicted to be strongest when relatedness within the colony is high, as in species with a single queen per colony (monogyne). In these cases, the reproductive individuals who are the recipients of worker helping behavior are more likely to carry the same allele for that behavior, with probability proportional to relatedness between worker and reproductive. In contrast, in species with multiple queens and lower relatedness, like weakly or highly polygyne ants, there is a higher chance that altruistic behavior benefits non‐relatives. These colony structures are predicted to weaken kin selection, leading to more relaxed selection on worker‐biased genes. We find some evidence in highly polygyne species that genes with worker‐biased expression experience more relaxed selection compared to queen‐biased or non‐differentially expressed genes. However, this pattern does not appear to hold consistently across species with lower or more variable queen numbers, where the degree of relaxed selection in worker genes shows no clear association with average queen number per nest. This may point to possible compensatory mechanisms present in these contexts to counteract relaxed selection in workers or that these predicted patterns are too subtle to be detected with current methods, highlighting areas of future study.